The causal effect of education on health: What is the role of health behaviors? - Giorgio Brunello; Margherita Fort; Nicole Schneeweis; Rudolf Winter-Ebmer (Institute for the Study of Labor (IZA), 2011)
In this paper we investigate the contribution of health related behaviors to the education gradient, using an empirical approach that addresses the endogeneity of both education and behaviors in the health production function. We apply this approach to a multi-country data set, which includes 12 European countries and has information on education, health and health behaviors for a sample of individuals aged 50+. Focusing on self reported poor health as our health outcome, we find that education has a protective role both for males and females. When evaluated at the sample mean of the dependent variable, one additional year of education reduces self-reported poor health by 7.1% for females and by 3.1% for males. Health behaviors - measured by smoking, drinking, exercising and the body mass index - contribute to explaining the gradient. We find that the effects of education on smoking, drinking, exercising and eating a proper diet account for at most 23% to 45% of the entire effect of education on health, depending on gender.
urn:nbn:de:101:1-201109288874
Keywords: J1; I12; I21; 330; health; education; health behaviors; Europe; Bildungsniveau; Gesundheit; Gesundheitsvorsorge; Europa